1997
DOI: 10.1021/bi962776b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Macromolecular Specificity of Human Plasma Phospholipid Transfer Protein

Abstract: Phospholipid transfer protein (PLTP), also known as lipid transfer protein 2 (LTP-2), mediates a transfer of phospholipids between high-density lipoproteins (HDL). The molecular and macromolecular specificities of recombinant human PLTP were studied using a fluorometric assay based on the excimer fluorescence of pyrenyl lipids. To determine lipoprotein specificity of PLTP, donor very low density lipoproteins (VLDL), low-density lipoproteins (LDL), and HDL were labeled with 1-palmitoyl-2-[10-(1-pyrenyl)decanoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 40 publications
(57 reference statements)
2
83
2
1
Order By: Relevance
“…When these results are considered with the data in Table IV, it follows that enrichment with TG destabilizes the apoA-I in rHDL. DISCUSSION The ability of PLTP to remodel HDL into large and small particles, mediate the dissociation of apoA-I from HDL, and transfer phospholipids between HDL and other lipoproteins is well documented (1)(2)(3)(4)(5)(6)(7)(8). Earlier work from this laboratory has also established that TG enrichment enhances the remodeling of HDL by PLTP (9).…”
Section: H (Closed Triangles)mentioning
confidence: 86%
See 1 more Smart Citation
“…When these results are considered with the data in Table IV, it follows that enrichment with TG destabilizes the apoA-I in rHDL. DISCUSSION The ability of PLTP to remodel HDL into large and small particles, mediate the dissociation of apoA-I from HDL, and transfer phospholipids between HDL and other lipoproteins is well documented (1)(2)(3)(4)(5)(6)(7)(8). Earlier work from this laboratory has also established that TG enrichment enhances the remodeling of HDL by PLTP (9).…”
Section: H (Closed Triangles)mentioning
confidence: 86%
“…1 transfers phospholipids (PL) between high density lipoproteins (HDL) and very low density lipoproteins as well as between different particles within the HDL fraction (1,2). It also remodels HDL into large and small particles in a process that is accompanied by the dissociation of lipid-poor or lipid-free apolipoprotein A-I (apoA-I) (3)(4)(5)(6)(7)(8).…”
Section: Phospholipid Transfer Protein (Pltp)mentioning
confidence: 99%
“…Phosphatidylcholines, a class of phospholipids, are the essential cholesterol-solubilizing components of HDL and the acyl donors for the esterification of FC into CE by LCAT (Rao et al, 1997). The elevated plasma PLTP activity during the negative energy balance in early lactation could represent a physiological reaction to counteract the low plasma cholesterol concentration by providing substrate for the LCAT reaction and thereby increasing the CE production in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Another early study found a larger proportion of SM in plasma chylomicrons than in chyle chylomicrons in humans, 12% versus 7% of the polar lipids (164), and in rat the proportion of SM is higher in plasma VLDL than in nascent VLDL (94,165). Whether this difference should be attributed to the action of lipases or differences in kinetics for the transfer of different polar lipids between lipoprotein classes is not known, although PLTP mediates the transfer of SM as well as glycerophospholipids (159,166). When VLDL was incubated with LPL, the level of g-migrating lipoprotein E increased, suggesting that these particles may be formed from surface material during lipolysis (167).…”
Section: Chylomicron and Vldl Smmentioning
confidence: 99%